A Fully Biodegradable Battery for Self‐Powered Transient Implants. Issue 28 (27th May 2018) - Huang, Xueying; Wang, Dan; Yuan, Zhangyi; Xie, Wensheng; Wu, Yixin; Li, Rongfeng; Zhao, Yu; Luo, Deng; Cen, Liang; Chen, Binbin; Wu, Hui; Xu, Hangxun; et al.
Abstract: Biodegradable transient devices represent an emerging type of electronics that could play an essential role in medical therapeutic/diagnostic processes, such as wound healing and tissue regeneration. The associated biodegradable power sources, however, remain as a major challenge toward future clinical applications, as the demonstrated electrical stimulation and sensing functions are limited by wired external power or wireless energy harvesters via near‐field coupling. Here, materials' strategies and fabrication schemes that enable a high‐performance fully biodegradable magnesium–molybdenum trioxide battery as an alternative approach for an in vivo on‐board power supply are reported. The battery can deliver a stable high output voltage as well as prolonged lifetime that could satisfy requirements of representative implantable electronics. The battery is fully biodegradable and demonstrates desirable biocompatibility. The battery system provides a promising solution to advanced energy harvesters for self‐powered transient bioresorbable implants as well as eco‐friendly electronics. Abstract : Biodegradable transient devices represent an emerging type of electronics. The associated biodegradable power sources, however, remain a major challenge toward future clinical applications. A high‐performance fully biodegradable magnesium–molybdenum trioxide battery is reported as an alternative approach as an in vivo on‐board power supply. The battery system provides a promising solution to advanced energy harvesters for self‐powered transient bioresorbable implants.